Impact of the COVID-19 Event on the Characteristics of Atmospheric Single Particle in the Northern China - Zheng Li; Jingjing Meng; Ling Zhou; Ruiwen Zhou; Mengxuan Fu; Yachen Wang; Yanan Yi; Aijing Song; Qingchun Guo; Zhanfang Hou; Li Yan (Aerosol and Air Quality Research)
Abstract The COVID-19 event triggered global attention which broke out at the end of 2019. To investigate the impact of the COVID-19 pandemic prevention and control actions on the chemical composition, size distribution, and mixing state of individual particles, real-time individual particles in the urban atmosphere of the Northern China were analyzed using single particle aerosol mass spectrometry (SPAMS) during January 16 to February 4, 2020. The results showed that the concentrations of PM2.5, NOx, and CO were lower during DP (during the pandemic) than those during BP (before the pandemic), while O3 concentration increased by about 40.9% during DP due to a lower concentration of NO2 restraining the decomposition of O3 via the reaction of NO with O3. The number count of carbonaceous particles during DP decreased by 20.2% compared to that during BP due to the sharp reduction of factory production and vehicular transportation during DP. Dust particles during DP exhibited weaker 23Na+, 56Fe+, and 79PO3− signals than those during BP, suggesting that dust particles during DP were mostly derived from mineral dust rather than industrial sources. The total particles during DP peaked at a larger size than those during BP, due to the higher fraction of secondary inorganic ions through the enhanced heterogeneous aqueous oxidation. The unscaled size distribution of total particles peaked at 0.50 µm during BP and at 0.66–0.70 µm during DP, suggesting that particles remained for a long time in the atmosphere and went through a strong aging process during DP. The single particles during DP were more aged than those during BP, owing to the stronger atmospheric oxidizing capacity during DP.